2022
DOI: 10.1017/s0967199421000939
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in mammalian X and Y sperm differences and sex control technology

Abstract: Summary Mammal sex determination depends on whether the X sperm or Y sperm binds to the oocyte during fertilization. If the X sperm joins in oocyte, the offspring will be female, if the Y sperm fertilizes, the offspring will be male. Livestock sex control technology has tremendous value for livestock breeding as it can increase the proportion of female offspring and improve the efficiency of livestock production. This review discusses the detailed differences between mammalian X and Y sperm with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…High adsorption capacity for Congo red and doxycycline was achieved due to the high surface area of ZIF8 and enhanced adsorbent‐pollutant contact by their autonomous motion [30] . MOFs has also been particularly valued in catalytic degradation of pollutants by integrating with active iron species [32] . Not only acting as pollutant degradation agent, Fe 3 O 4 can also be exploited for fuel decomposition so as to produce bubbles for enhanced propulsion [33–34] .…”
Section: Introductionmentioning
confidence: 99%
“…High adsorption capacity for Congo red and doxycycline was achieved due to the high surface area of ZIF8 and enhanced adsorbent‐pollutant contact by their autonomous motion [30] . MOFs has also been particularly valued in catalytic degradation of pollutants by integrating with active iron species [32] . Not only acting as pollutant degradation agent, Fe 3 O 4 can also be exploited for fuel decomposition so as to produce bubbles for enhanced propulsion [33–34] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Iron‐based metal–organic frameworks, for instance, may exhibit heterogeneous Fenton‐like behavior that is important for environment remediation. [ 9,13–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…NH 2 ‐MIL‐88B have been applied as a naked‐eye sensor of organic vapors, drug delivery systems, and catalyst for reactions that include photocatalytic CO 2 reduction, reduction of chromium, and aerobic oxidation of alcohols. [ 1,13–17,20 ] However, it was found that the magnetic iron‐based materials have a strong tendency to agglomerate, which will reduce their catalytic activity. [ 21 ] Nevertheless, Chen et al suggested that the agglomeration can be reduced by the incorporation of carbonaceous sheets to the material.…”
Section: Introductionmentioning
confidence: 99%